The Influence of Western Drama on Contemporary African Drama - Osameka Oyindamola Mercy; Eze Mabel Nkechinyere (MultiTech Publisher, 2024)
African drama is generally believed to find its roots in the tradition and culture of the African society such as the celebration of the new yam festival (festivity) the display of masquerade, religious rituals, and the moonlight story (storytelling) therefore, African drama has been in existence before the emergence of the colonialism, African drama existed in form of action, through music and dance that was ritualized to express emotions such as terror, passion, and love. These actions were imitations of what the people wanted to happen so if they wanted to kill an enemy they would act out the process, religious and magical rituals were used and combined with dance and songs, with the emergence of Western drama which was brought through colonization, African drama became modernized to scripting of drama, use of language satirical plays, use of a curtain, theatre of the absurd, during colonialism, African drama such as the religious ritual was seen as a barbaric act by the colonial masters. The influence of this Western drama on African drama gave birth to what we call contemporary African drama. As we read the background and other parts of this paper we will understand the influence of Western drama on contemporary African drama.